2013
DOI: 10.1038/hr.2013.74
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aldosterone breakthrough on albuminuria during treatment with a direct renin inhibitor and combined effect with a mineralocorticoid receptor antagonist

Abstract: We have reported observing aldosterone breakthrough in the course of relatively long-term treatment with renin-angiotensin (RA) system inhibitors, where the plasma aldosterone concentration (PAC) increased following an initial decrease. Aldosterone breakthrough has the potential to eliminate the organ-protective effects of RA system inhibitors. We therefore conducted a study in essential hypertensive patients to determine whether aldosterone breakthrough occurred during treatment with the direct renin inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Redundancies that bypass our therapeutic blockade or inadvertent suppression of beneficial components of this system might reduce the efficacy of our RAAS suppressive therapies. For example, Angiotensin II and aldosterone levels occasionally rise despite pharmacologic RAAS suppression, and the underlying mechanisms are still not well understood . Furthermore, Some drugs and strategies used to treat cardiovascular disease, including furosemide, amlodipine, hydralazine and dietary sodium restriction, stimulate the RAAS (Supporting Information Figure S1).…”
Section: Introductionmentioning
confidence: 99%
“…Redundancies that bypass our therapeutic blockade or inadvertent suppression of beneficial components of this system might reduce the efficacy of our RAAS suppressive therapies. For example, Angiotensin II and aldosterone levels occasionally rise despite pharmacologic RAAS suppression, and the underlying mechanisms are still not well understood . Furthermore, Some drugs and strategies used to treat cardiovascular disease, including furosemide, amlodipine, hydralazine and dietary sodium restriction, stimulate the RAAS (Supporting Information Figure S1).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, multiple studies have shown that add-on therapy with an MR antagonist reduces albuminuria in humans with type 2 diabetes on an ACEI, ARB, or renin inhibitor [59][60][61]. Further, low-dose spironolactone was recently shown to exert significant lowering of blood pressure and urinary albumin creatinine ratio in high-risk patients with resistant hypertension and type 2 diabetes [62].…”
Section: Mr and Diabetic Complications In Humansmentioning
confidence: 97%
“…Aldosterone breakthrough usually does not influence the antihypertensive effects of RAS inhibitors, but breakthroughed aldosterone attenuates the organ-protective effects of RAS inhibitors through the actions of mineralocorticoid receptors (MRs). [18][19][20][21][22][23] With relatively long-term treatment with RAS inhibitors, regardless of dose or combination of drugs, aldosterone breakthrough may be impossible to prevent. Inadequate blockade of aldosterone may be one of the reasons why long-term administration of RAS inhibitors may not be sufficiently effective in patients with DM nephropathy.…”
Section: Introductionmentioning
confidence: 98%